Exploring the Impact of Cerebrovascular Disease and Major Depression on Non-diseased Human Tissue Transcriptomes - Poon, Chi-Lam; Chen, Cho-Yi (Frontiers in Genetics, 2021)
Background: The development of complex diseases is contributed by the combination of multiple factors and complicated interactions between them. Inflammation has recently been associated with many complex diseases and may cause long-term damage to the human body. In this study, we examined whether two types of complex disease systematically altered the transcriptomes of non-diseased human tissues and whether inflammation was linked to identifiable molecular signatures, using post-mortem samples from the Genotype-Tissue Expression (GTEx) project. Results: Following a series of differential expression (DE) analyses, dozens to hundreds of DE genes were identified in multiple tissues between subjects with and without a history of cerebrovascular disease (CVD) or major depression (MD). DE genes from these disease-associated tissues—the visceral adipose, tibial artery, caudate, and spinal cord for CVD; and the hypothalamus, putamen, and spinal cord for MD—were further analyzed for functional enrichment. Many pathways associated with immunological events were positively enriched in the DEGs of the CVD-associated tissues, as were the neurological and metabolic pathways in the MD-associated tissues. Eight gene–tissue pairs were found to overlap with those prioritized by our transcriptome-wide association studies (TWAS), indicating a potential genetic effect on gene expression for circulating cytokine phenotypes. Conclusions: Complex diseases like CVD and MD may cause observable changes in the gene expression of non-diseased tissues, suggesting that a long-term impact of diseases, lifestyles and environmental factors may together contribute to the appearance of transcriptomic “scars” on the human body. Furthermore, inflammation is probably one of the systemic and long-lasting effects of cerebrovascular events.